CATEGORIZATION OF RAILWAY STATIONS AND STOPS AND ITS APPLICATION (Perner's Contacts, 2014)
The article introduces universally applicable instrument for railway personal transport tariff point categorization, which has a potential to become a decisionsupport instrument, which could be used for setting a fee for tariff point use or for determination of optimal equipment of the station building. The instrument intentionally uses easily acquirable and definite inputs. The output is a point-rating of the station supplemented by characteristic signs, allowing universal further usage.
Keywords: railway transport; tariff point categorization; railway station buildings